Intranasal methylene blue administration confers neuroprotection in rats subjected to exhaustive exercise training - Peng, Guangcong; Pan, Wenxin; Cai, Ziheng; Lin, Long; Ma, Xu (Frontiers in Behavioral Neuroscience, 2025)
IntroductionEmerging evidence suggests that exercise-induced fatigue negatively affects nervous system function, yet effective mitigation strategies are limited. This study aimed to determine whether intranasal methylene blue (MB) could prevent neurological deficits induced by exhaustive exercise in a rat model.MethodsWe utilized a rat exhaustive exercise training paradigm. Animal body weight was monitored, and a battery of behavioral tests was conducted to evaluate locomotor activity, anxiety-like behaviors, and spatial learning and memory. At the cellular level, we assessed neuron loss, apoptosis, synaptic proteins, myelin sheath, gliosis, and mitochondrial morphology in the hippocampal CA1 region and the striatum.ResultsRats subjected to exhaustive exercise exhibited reduced locomotor activity, increased anxiety-like behaviors, and impaired spatial memory. This was associated with significant neuron loss, activation of apoptotic pathways, loss of synaptic proteins and myelin sheath, gliosis, and compromised mitochondrial morphology in the hippocampus and striatum. Notably, intranasal MB treatment significantly rescued these neuronal damages and improved performance in behavioral tests.DiscussionOur findings demonstrate the neuroprotective effects of intranasal MB against exhaustive exercise-induced neurological deficits. This suggests that MB is a promising therapeutic agent for preventing the adverse neurological consequences of extreme physical exertion.